Specifics of ownership rights in endowment funds according to the norms of the draft law of the Republic of Kazakhstan “On target capital foundations (endowment funds)” - Kuanganov Ф.Ш.; Kizdarbekova А.С.; Makenov Т.К. (BULLETIN of L.N. Gumilyov Eurasian National University Law Series, 2024)
The article considers the questions about the content of ownership rights to property gifted to endowment funds in accordance with the norms of the draft law of the Republic of Kazakhstan “On endowment funds”, and the implementation of this right in practice. For these purposes, a theoretical analysis of issues about the subjects and objects of the new category of property rights, as well as the content of property rights in the context of the current rules governing the institution of trust management, was carried out, and issues of implementing innovations related to the activities of endowment funds were analyzed. By analyzing the powers of the owner, some essential characteristics and signs of a new category of property rights have been identified, distinguishing this category from other forms of property rights and property rights in general; the right of ownership of endowments is defined as a special property right that has specific features of title ownership, ensuring legislative recognition, protection and use of the property powers of the owner, even in the case of transfer under a trust management agreement of all three powers of ownership, use and disposal of property. In the Conclusion, the authors made specific conclusions based on the results of the issues considered.